Obesity, lifestyle risk-factors, and health service outcomes among healthy middle-aged adults in Canada - Alter David A; Wijeysundera Harindra C; Franklin Barry; Austin Peter C; Chong Alice; Oh Paul I; Tu Jack V; Stukel Therese A (BMC Health Services Research, 2012)
Abstract Background The extent to which uncomplicated obesity among an otherwise healthy middle-aged population is associated with higher longitudinal health-care expenditures remains unclear. Methods To examine the incremental long-term health service expenditures and outcomes associated with uncomplicated obesity, 9398 participants of the 1994–1996 National Population Health Survey were linked to administrative data and followed longitudinally forward for 11.5 years to track health service utilization costs and death. Patients with pre-existing heart disease, those who were 65 years of age and older, and those with self-reported body mass indexes of <18.5 kg/m2 at inception were excluded. Propensity-matching was used to compare obesity (+/− other baseline risk-factors and lifestyle behaviours) with normal-weight healthy controls. Cost-analyses were conducted from the perspective of Ontario’s publicly-funded health care system. Results Obesity as an isolated risk-factor was not associated with significantly higher health-care costs as compared with normal weight matched controls (Canadian $8,294.67 vs. Canadian $7,323.59, P = 0.27). However, obesity in combination with other lifestyle factors was associated with significantly higher cumulative expenditures as compared with normal-weight healthy matched controls (CAD$14,186.81 for those with obesity + 3 additional risk-factors vs. CAD$7,029.87 for those with normal BMI and no other risk-factors, P < 0.001). The likelihood that obese individuals developed future diabetes and hypertension also rose markedly when other lifestyle factors, such as smoking, physical inactivity and/or psychosocial distress were present at baseline. Conclusions The incremental health-care costs associated with obesity was modest in isolation, but increased significantly when combined with other lifestyle risk-factors. Such findings have relevance to the selection, prioritization, and cost-effective targeting of therapeutic lifestyle interventions.